Evaluasi kinerja organisasi dan strategi penyelenggaraan pendidikan seksual pada peserta didik di Madrasah Aliyah Negeri Kendal - Navaron, Attan (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Sexual education services for school-age children are important educational services because they are related to increasing knowledge about adolescent sexuality, preventing sexual violence and preventing early marriage and transmission of sexual diseases. The purpose of this study is to conduct an analysis of the performance evaluation of sexual education conducted on students at MAN Kendal and 2) to recommend solutions to increase knowledge and understanding of sexual education in students at MAN Kendal. The research method used is qualitative. The results of the study are as follows: 1) the use of seminars as a means of self-development for students is considered ineffective because to make behavior changes in students it is necessary to transfer knowledge and habituation to be able to implement this knowledge in life, 2) The solution to provide sexual education to students is to integrate the subjects in schools so that a sexual education curriculum can be designed that suits the needs of students, the methods used and the outputs and outcomes expected from sexual education. The strategy that will be used in conducting sexual education for students at MAN Kendal is using SWOT analysis especially strength-opportunity strategy. Strength-opportunity are the combination between internal factor namely strength to get the optimal ways in achieving the opportunity. Conclusion: Sexual education for students in MAN Kendal must be developed in accordance with the needs of knowledge and protection efforts for students.